Reconsidering the need for gain-of-function research on enhanced potential pandemic pathogens in the post-COVID-19 era - Shinomiya, Nariyoshi; Minari, Jusaku; Yoshizawa, Go; Dando, Malcolm; Shang, Lijun (Frontiers in Bioengineering and Biotechnology, 2022)
The dual-use risk of infectious disease research using enhanced potential pandemic pathogens (ePPP), particularly gain-of-function (GOF) research, has been debated since 2011. As of now, research is supported on the condition that the research plan is reviewed and the actual experiment is supervised. However, the kinds of research conducted and what benefits they have brought to our society have not been adequately verified. Nevertheless, due to the COVID-19 pandemic that began at the end of 2019 and caused numerous deaths and wide economic disruption, the importance of infectious disease control from an international perspective has been recognized. Although complete control of the pandemic is still far off, positive signs include generating epidemiological trends based on genome analysis, therapeutic drug and vaccine development, clinical patient management, and public health policy interventions. In this context, the time has come to reconsider the true significance of GOF research on ePPP and the state of research governance in the post-COVID-19 era. In particular, the risks of such research are clearer than before, whereas its benefits seem less apparent. In this paper, we summarize the history of discussions on such GOF research, its significance in the light of the current COVID-19 pandemic, and the direction we shall take in the future.